2010
DOI: 10.1002/pola.24454
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cationic N‐[3‐(dimethylamino)propyl]methacrylamide brushes on silicon wafer via surface‐initiated RAFT polymerization

Abstract: Surface-initiated reversible addition-fragmentation chain transfer (SI-RAFT) polymerization of N-[3-(dimethylamino)propyl]methacrylamide (DMAPMA) on the silicon wafer was conducted in attempt to create controllable cationic polymer films. The RAFT agent-immobilized substrate was prepared by the silanization of hydroxyl groups on silicon wafer with 3-aminopropylthriethoxysilane (APTS) and by the amide reaction of amine groups of APTS with ester groups of 4-cyano-4-((thiobenzoyl) sulfanyl) pentanoic succinimide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 46 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…The immobilization of CPAD onto the allylamine layer was also confirmed by the appearance of a S 2p peak curve fitted to two components with binding energies at about 162.5 eV (C-S) and 161.4 eV (C_S). The thickness of the Si\NH 2 and Si-CPAD layers were measured by ellipsometry to be 0.6±0.3 nm and 1.7 ±0.5 nm, respectively, these values are consistent with literature data [12]. The surface morphologies of the Si\H substrate after allylamine and CPAD immobilizations are shown in Fig.…”
Section: Functionalization Of the Hydrogen-terminated Silicon Wafer Amentioning
confidence: 77%
See 2 more Smart Citations
“…The immobilization of CPAD onto the allylamine layer was also confirmed by the appearance of a S 2p peak curve fitted to two components with binding energies at about 162.5 eV (C-S) and 161.4 eV (C_S). The thickness of the Si\NH 2 and Si-CPAD layers were measured by ellipsometry to be 0.6±0.3 nm and 1.7 ±0.5 nm, respectively, these values are consistent with literature data [12]. The surface morphologies of the Si\H substrate after allylamine and CPAD immobilizations are shown in Fig.…”
Section: Functionalization Of the Hydrogen-terminated Silicon Wafer Amentioning
confidence: 77%
“…RAFT-mediated polymerization of VBTAC from the RAFT agent-immobilized silicon surface was accomplished in the presence of CPAD as a free RAFT agent. It has been reported that the addition of free RAFT agent is required to render the system heterogeneous and slow down the reaction activity [12]. Moreover, introduction of free RAFT agent allows for formation of polymer in solution.…”
Section: Raft-mediated Polymerization Of Vbtac On the Functionalized mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the utilization of S‐RAFT for the preparation of well‐defined polymer brushes on planar substrates has not been extensively investigated in comparison with other CRP techniques. Nevertheless, the inherent versatility and functional group tolerance of the S‐RAFT process are attractive and have recently been exploited by Advincula and coworkers17 and Caykara and coworkers 18. They reported the synthesis of polymer brushes grafted from electropolymerized polythiophene RAFT agent surfaces and cationic N ‐[3‐(dimethylamino)propyl]methacrylamide brushes on silicon substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Several LRP techniques have been reported for preparation polymer functionalized surfaces, such as nitroxide-mediated radical polymerization (Bian & Cunningham, 2006;Cimen & Caykara, 2012), atom transfer radical polymerization (Bai, Zhang, Cheng, & Zhu, 2012;Bian & Cunningham, 2006;Turan, Demirci, & Caykara, 2010), reversible addition-fragmentation chain transfer (RAFT) polymerization (Demirci & Caykara, 2012;Gurbuz, Demirci, Yavuz, & Caykara, 2011;Jiang & Xu, 2013) and single-electron transferliving radical polymerization (Demirci, Kinali-Demirci, & Caykara, 2013;Percec et al, 2006). LRP provides excellent control over the molecular weight and polydispersity of graft polymers (Braunecker & Matyjaszewski, 2007;Dietrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%